1994
DOI: 10.1177/109019819402100304
|View full text |Cite
|
Sign up to set email alerts
|

Learner Developed Materials: An Empowering Product

Abstract: Freire used very specific materials in culture circles to support an empowering process that allowed learners to define the content and outcome of their own learning. However, the materials themselves were carefully crafted and developed by Freire and his co-workers. This article focuses on an extension of Freire's problem-posing educational methods to include participant involvement in the development and production of their own learning materials. Four linked case examples, one in literacy and three in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 9 publications
2
65
0
1
Order By: Relevance
“…It contains concrete language presented in an organized layout, and includes culturally diverse, text-enhancing graphics. (15)(16)(17)(18)(19) It contains the same advance care planning topics as the aforementioned standard form. However, it also contains broader treatment choices, such as providing more options than just to prolong or not to prolong life (the options available in the standard form), but also the options of wanting to prolong life but only for a period of time, being able to refuse certain treatments such as blood transfusions, and having the option of letting the health care agent decide.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains concrete language presented in an organized layout, and includes culturally diverse, text-enhancing graphics. (15)(16)(17)(18)(19) It contains the same advance care planning topics as the aforementioned standard form. However, it also contains broader treatment choices, such as providing more options than just to prolong or not to prolong life (the options available in the standard form), but also the options of wanting to prolong life but only for a period of time, being able to refuse certain treatments such as blood transfusions, and having the option of letting the health care agent decide.…”
Section: Interventionmentioning
confidence: 99%
“…midprimary educational level. We also incorporated input from the target population (15) and used a clear layout, large 14 point font, appropriate line spacing and margins, and graphics that helped to explain the text. (14,(16)(17)(18)(19) These techniques have been shown to improve acceptability (16,17), activate patients to initiate discussions with providers (17) and, in some cases, enhance understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural barriers to screening are also important for black women as suggested by the effectiveness of culturally tailored videos and classroom instruction on screening mammography rates. Previous research has shown that patient involvement in developing health education materials ensures that the content of the materials is relevant to the patients' situation and is presented from their point of view (Rudd and Comings 1994).…”
Section: Screeningmentioning
confidence: 99%
“…This reinforces the finding of Rudd and Comings that patient involvement in developing health education materials ensures that the content is relevant to the patients' situation and is presented from their viewpoint. 19 Women in our focus groups 15 helped write and acted in the video; in addition, a woman in one focus group was hired as the peer educator. The effectiveness of our woman-to-woman program and video supports findings of focus groups of older African American women in the North Carolina Save Our Sisters Project that women turn to women they know with their health concerns.…”
Section: Discussionmentioning
confidence: 99%